Optimalisasi Zakat Produktif Melalui Program Ternak Kambing Bergulir dalam Pemberdayaan Mustahik di LAZISNU Pati - Zaim Imron Rosadi; Suparwi S (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the management of the Rolling Goat Farming Program as an implementation of productive zakat in empowering mustahik at LAZISNU Pati Regency. This research used a qualitative field research approach. Data were collected through observation, interviews, and documentation involving mustahik, program managers, assistants, and supporting informants. Data analysis employed the Miles and Huberman interactive model with source and technique triangulation. The results show that the program has been supported by Standard Operating Procedures (SOP) and a rolling mechanism. However, assistance, monitoring, and risk management have not been fully optimal. Mustahik still face obstacles such as limited feed availability, livestock diseases, and limited technical capacity in livestock management. In addition, the rolling mechanism has not been consistently implemented, affecting program sustainability. Nevertheless, the program contributes positively to increasing productive assets and strengthening mustahik business capacity. Therefore, strengthening assistance and monitoring systems is necessary to improve program sustainability.